International study on impact of COVID‐19 on cardiac and thoracic aortic aneurysm surgery. Issue 5 (13th August 2020) - Idhrees, Mohammed; Bashir, Mohamad; Mousavizadeh, Mostafa; Hosseini, Saeid
Abstract: Background: The coronavirus disease‐2019 (COVID‐19) pandemic gripped every nation's health care system and provisions on all levels. In cardiac and aortic surgery, as it is with most specialities, elective surgeries were halted. Aims of the study: We captured reflections, contingencies, and current practices across of high‐volume centers in cardiac and aortic surgery globally. We also aimed this study to assess decision on prioritization of the surgical patients, the need for personal protection equipment, and the choice of preoperative investigations in current dynamic and fluid climate. Methods: A validated web‐based questionnaire was constructed and was circulated to the international surgeons amongst high volume cardiac and aortic surgery centers. Their intrinsic feedback on decision making, the impact of the lockdown, and perspectives for the future ahead of us all were noted. A mixed‐method approach was constructed. Qualitative data analysis was introduced to signify the impact globally. Results: Overall, 23 centers from 18 countries participated in this international study. About 91.7% of the respondents stopped operating on elective patients during the pandemic. The majority of the surgeons agreed that acute aortic dissection (87.1%) should be operated as an emergency procedure and stable triple vessel disease (87.1%) to be considered as an elective procedure. Three‐fifth (60%) of the respondents relied on computerized tomography chest as a preoperative screening modality. Conclusion: In the present climate where there is a paucity of evidence, this will give an interim consensus for the cardiac surgeons. With the increase in the cumulative number of patients with COVID‐19, careful utilization of the resources regarding hospital beds and manpower is of paramount importance.